2023
DOI: 10.1093/mmy/myad030
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing ofCandida haemuloniispecies complex from Brazil and the United States: Genetic diversity and antifungal susceptibility

Abstract: Candida haemulonii complex species can be multidrug-resistant (MDR) and cause infections such as candidemia. This study determined the genetic relationship between isolates from Brazil and the United States through whole-genome sequencing and performed antifungal susceptibility testing to investigate drug resistance. Contrary to what is widely described, most isolates were susceptible to azoles. However, an atypical susceptibility profile was found in 50% of C. pseudohaemulonii strains including resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…These species frequently exhibit resistance to azoles and AMB [21,46]. However, a recent study indicated that a majority (44/46) of C. haemulonii complex strains from the US and Brazil were susceptible to azoles [49]. Additionally, all four C. pseudohaemulonii from the US were susceptible to both AMB and azoles, whereas two of the four isolates were resistant to the three echinocandins [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These species frequently exhibit resistance to azoles and AMB [21,46]. However, a recent study indicated that a majority (44/46) of C. haemulonii complex strains from the US and Brazil were susceptible to azoles [49]. Additionally, all four C. pseudohaemulonii from the US were susceptible to both AMB and azoles, whereas two of the four isolates were resistant to the three echinocandins [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study indicated that a majority (44/46) of C. haemulonii complex strains from the US and Brazil were susceptible to azoles [49]. Additionally, all four C. pseudohaemulonii from the US were susceptible to both AMB and azoles, whereas two of the four isolates were resistant to the three echinocandins [49]. In our study, AMB and fluconazole resistance were observed in 77.8% and 44.4% of C. haemulonii complex samples from Korean hospitals, respectively.…”
Section: Discussionmentioning
confidence: 99%